Energy and exergy analyses of S–CO2 coal-fired power plant with reheating processes. (15th November 2020) - Chen, Zhewen; Wang, Yanjuan; Zhang, Xiaosong
Abstract: S–CO2 (Supercritical-CO2 ) coal-fired power plant is a promising technology for efficient and clean utilization of coal for power generation. The conversion and transfer of the energy and exergy in the power plants with double-reheat and single-reheat processes are studied. With the main gas parameters of 32 MPa/893.15 K, the power generation efficiencies of the S–CO2 coal-fired power plant with double-reheat and single-reheat processes are 49.06% and 48.72%, respectively. The corresponding exergy efficiencies are 48.02% and 47.69%, respectively. The origins of exergy destructions in different units are studied using the Energy Utilization Diagram (EUD) method. The exergy distributions of the power plants are presented. For the power plant with double-reheat process, the work output, the exergy exhaust into the atmosphere, the exergy destruction in combustion process, the exergy destruction in heat transfer processes, the exergy destruction caused by pressure loss, and the exergy destructions in turbo systems account for 48.02%, 9.66%, 20.45%, 17.56%, 1.08%, and 3.23% of the total exergy input of the power plant, respectively. Highlights: The exergy distribution of S–CO2 coal-fired power plant is presented. Origins of exergy destructions in different processes are revealed. Combustion causes the largest exergy destruction in the power plant. Exergy destructions caused by pressure losses are calculated.